Cost-Benefit Analysis of Transitional Care in Neurosurgery. Issue 5 (28th September 2018) - Liu, Jingyi; Gormley, Natalia; Dasenbrock, Hormuzdiyar H; Aglio, Linda S; Smith, Timothy R; Gormley, William B; Robertson, Faith C
Abstract: BACKGROUND: Transitional care programs (TCPs) coordinate care to improve safety and efficiency surrounding hospital discharge. While TCPs have the potential to reduce hospital length of stay and readmissions, their financial implications are less well understood. OBJECTIVE: To perform a cost-benefit analysis of a previously published neurosurgical TCP implemented at an urban academic hospital from 2013 to 2015. METHODS: Patients received intensive preoperative education and framing of expectations for hospitalization, in-hospital discharge planning and medication reconciliation with a nurse educator, and a follow-up phone call postdischarge. The cost-benefit analysis involved program costs (nurse educator salary) and total direct hospital costs within the 30-d perioperative window including readmission costs. RESULTS: The average cost of the TCP was $435 per patient. The TCP was associated with an average total cost reduction of 17.2% (95% confidence interval [CI]: 7.3%-26.7%, P  = .001). This decrease was driven by a 14.3% reduction in the average initial admission cost (95% CI: 6.2%-23.7%, P  = .001), largely attributable to the 16.3% decrease in length of stay (95% CI: 9.93%-23.49%, P  < .001). Thirty-day readmissions were significantly decreased in the TCP group, with a 5.5% readmission rate for controls and 2.4% for TCP enrollees ( P  = .04). The average cost of readmission was decreased by 71.3% (95% CI: 58.7%-74.7%, P  < .01). CONCLUSION: This neurosurgical TCP was associated with decreased costs of initial admissions, 30-d readmissions, and total costs of hospitalization alongside previously published decreased length of stay and reduced 30-d readmission rates. These results underscore the clinical and financial feasibility and impact of transitional care in a surgical setting.